The Effect of L-Arginine on Diameter of Spiral Artery and Fetal Weight between Normal Pregnant Mice and Preeclampsia Mouse Models - Aditiawarman, - (Advanced Scientific Research, 2020)
L-Arginine is a semi-essential amino acid, which is one of the nitric oxide (NO) synthesis substrates. This compound has a role in the L-Arginine-NO pathway in preeclampsia. This study determined the effect of L-Arginine on the diameter of the spiralis artery and fetal weight in normal pregnant mice and preeclampsia mice model. A true experimental study with randomized post-test-only control group using Swiss Mus musculus divided into 3 groups. There were normal pregnant mice group (K-), preeclampsia mouse model group (K+), and preeclampsia mouse models with L-Arginine group (P). The mean of fetal weight of each mouse was calculated and measured the diameter of the spiralis artery from placental. The mean diameter of the spiral arteries of the groups (K-), (K+) and (P) was 221.7500±70.2498µm, 159.4333±30.2653µm, and 277.3222±54.5503µm, respectively. There were significant differences between groups (K-) and (K+) (p = 0.024), groups (K-) and (P) (p = 0.047), and between groups (K+) and (P) (p = 0.000). Meanwhile, the mean fetal weight of the groups (K-), (K+) and (P) was 0.6733±0.3145g, 0.6222±0.2838g, and 0.7589±0.3444g, respectively. There were no significant differences between groups (K-) and (K+) (p = 0.722), between groups (K-) and (P) (p = 0.590), and between groups (K +) and (P) (p = 0.372). L-Arginine has been proven effective in repairing endothelial damage and was seen from the diameter of the spiralis artery and fetal weight in preeclampsia mouse models.